Problem and needs analysis for the development of traffic safety education for elementary school students in Yogyakarta - Erviana, Vera Yuli; Wijaya, Oktomi; Suryanto, Farid (Institute of Advanced Engineering and Science, 2024)
The establishment of a traffic safety culture in Indonesia is a challenge, and there are many factors that contribute to this difficulty. To instill awareness and culture, the concept is taught through education from an early age. Therefore, this study aimed to develop traffic safety education for elementary school students in Yogyakarta using a qualitative approach. Data were obtained through four focus group discussion (FGD) sessions with school principals, teachers, parents, and school security officers. The analysis was conducted by transcribing, extracting important statements, formulating meanings, and categorizing the findings into themes. The results showed four themes from the analysis, such as unsafe behavior, education content, teaching methods, and stakeholder support. Traffic safety education was taught from an early age to elementary school students, and the content was delivered using appropriate teaching methods. The success of education required support from different parties in Yogyakarta City.